2017
DOI: 10.1016/j.abb.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of sulfenic acids in cellular redox signaling: Reconciling chemical kinetics and molecular detection strategies

Abstract: The reversible oxidation of protein cysteine residues is well recognized as an important regulatory mechanism in redox-dependent cell signaling. Cysteine oxidation is diverse in nature and involves various post-translational modifications (sulfenic acids, disulfides, etc.) and the specific functional or structural impact of these specific oxidative events is still poorly understood. The proximal product of protein cysteine oxidation by biological reactive oxygen species (ROS) is sulfenic acid (Cys-SOH), and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 80 publications
1
33
1
Order By: Relevance
“…These findings are in line with the prevailing view that ROS act as biological messengers principally through reversible modification of sensitive surface cysteine residues on proteins (7,12). Recently developed methodologies now allow for the identification and quantification of redox-modified protein cysteine residues in intact cells and living tissue (44 -46).…”
Section: Molecular Targets Of Thermogenic Rossupporting
confidence: 73%
“…These findings are in line with the prevailing view that ROS act as biological messengers principally through reversible modification of sensitive surface cysteine residues on proteins (7,12). Recently developed methodologies now allow for the identification and quantification of redox-modified protein cysteine residues in intact cells and living tissue (44 -46).…”
Section: Molecular Targets Of Thermogenic Rossupporting
confidence: 73%
“…S -glutathionylation) for EGFR regulation is unknown, and it is plausible that these redox modifications might also affect subcellular EGFR trafficking. The cellular mechanisms that mediate EGFR (and other protein) cysteine oxidation are not fully understood[242]. While original studies suggested the involvement of NOX2 in the context of ligand-dependent stimulation, alternative mechanisms of EGFR transactivation involve DUOX1 [148, 243].…”
Section: Duox1 Silencing Emt and Altered Egfr Dynamics: A Dangerousmentioning
confidence: 99%
“…Unlike protein tyrosine phosphatases, where the primary oxidation target is the catalytic cysteine at the active site such that oxidation is always inhibitory, kinase families tend to have non-catalytic cysteine residues in unique locations specific to individual kinase families. Thus, function-altering oxidation of kinases can impose a spectrum of changes in structure and function [20, 60] thereby impacting activity, stability or interaction with partner proteins. This is why kinase oxidation can lead to either inhibition or activation depending on the specific protein.…”
Section: Discussionmentioning
confidence: 99%